Tailoring the optical and dynamic properties of iminothioindoxyl photoswitches through acidochromism - Medved', Miroslav; Hoorens, Mark W H; Di Donato, Mariangela; Laurent, Adèle D; Fan, Jiayun; Taddei, Maria; Hilbers, Michiel; Feringa, Ben L; Buma, Wybren Jan; Szymanski, Wiktor (Chemical science, 2021)
Multi-responsive functional molecules are key for obtaining user-defined control of the properties and functions of chemical and biological systems. In this respect, pH-responsive photochromes, whose switching can be directed with light and acid-base equilibria, have emerged as highly attractive molecular units. The challenge in their design comes from the need to accommodate application-defined boundary conditions for both light- and protonation-responsivity. Here we combine time-resolved spectroscopic studies, on time scales ranging from femtoseconds to seconds, with density functional theory (DFT) calculations to elucidate and apply the acidochromism of a recently designed iminothioindoxyl (ITI) photoswitch. We show that protonation of the thermally stable Z isomer leads to a strong batochromically-shifted absorption band, allowing for fast isomerization to the metastable E isomer with light in the 500-600 nm region. Theoretical studies of the reaction mechanism reveal the crucial role of the acid-base equilibrium which controls the populations of the protonated and neutral forms of the E isomer. Since the former is thermally stable, while the latter re-isomerizes on a millisecond time scale, we are able to modulate the half-life of ITIs over three orders of magnitude by shifting this equilibrium. Finally, stable bidirectional switching of protonated ITI with green and red light is demonstrated with a half-life in the range of tens of seconds. Altogether, we designed a new type of multi-responsive molecular switch in which protonation red-shifts the activation wavelength by over 100 nm and enables efficient tuning of the half-life in the millisecond-second range.